Formation of sociocultural identity of students of sports fields of training in the conditions of student communities in the aspect of sociological analysis - Ivanova I.Yu. ,; Belomestnova M.E. ,; Yevtushenko I.N. ,; Artemenko B.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the state and possible ways to solve the problem of forming the sociocultural identity of students in sports fields of study at pedagogical and non-pedagogical universities in the process of organizing and operating student communities. Methods and structure of the study. An analysis of the theoretical aspects of the problem under study was carried out in different contexts; data was also collected and analyzed on an online platform using a questionnaire developed by the authors as a research tool. Results and conclusions. Data were collected on the areas of activity, the involvement of students of higher educational institutions with a sports orientation of pedagogical and non-pedagogical training profiles in the organization and inclusion of them in various communities and associations, on the influence of these groups on the formation of sociocultural identity, values and norms of the future professional community, further self-determination and self-actualization in professions. The results of the study show the prevalence of negative trends in the student environment, insufficient organization and involvement of students in the activities of student communities and associations.